Determinants of Service Quality and Price on Student Satisfaction with College Foodservice - Bremantie, Ditha Pradnya; Saleh, Choirul; Mindarti, Lely Indah (Journal of Indonesian Tourism and Development Studies, 2026)
This study aimed to examine the influence of service quality and price perception on customer satisfaction at the Universitas Brawijaya Canteen, Indonesia, by analyzing the effects of tangibles, reliability, and empathy as SERVQUAL dimensions, as well as price suitability in terms of quality, perceived benefits, and affordability. Using a quantitative explanatory approach, data were collected from 133 respondents across two UB canteen locations through a structured questionnaire and analyzed using multiple linear regression. The results showed that empathy, price-to-benefit, and price-to-affordability had significant positive effects on customer satisfaction, while tangibles, reliability, and price-to-quality did not have significant partial effects; however, all variables simultaneously influenced satisfaction, with an Adjusted R² of 0.486. These findings indicate that emotional interaction and value-based price perceptions are more critical determinants of satisfaction in campus foodservice settings than physical facilities or technical service consistency. This study highlighted the limited empirical research on campus foodservice satisfaction in Indonesian universities using a focused SERVQUAL and price perception framework. The study contributes theoretically by refining SERVQUAL application in higher education foodservice and practically by providing evidence-based insights to support service improvement and pricing strategies for sustainable campus canteen management.